Edukasi Menemukan Ide Penelitian Melalui Pemanfaatan Aplikasi Berbasis Web Untuk Mahasiswa D3 RMIK - Wahyuni, Titin; Faida, Eka Wilda (STIKES Yayasan RS.Dr.Soetomo, 2023)
Students with Medical Records and Health Information have a short time to complete their final assignment, graduation demands are determined by an exit exam, so students must move quickly and efficiently in completing their final assignment. Therefore, this social service aims to increase student readiness in completing the final project by utilizing web-based applications. The targets of this activity are fourth and sixth semester students of D3 Medical Records and Health Information. The method in this activity is carried out by screening web-based applications that will be socialized and the implementation stage. The implementation of the activity was carried out on May 20, 2023. As a result of this activity students felt very useful by holding this activity and hoped that there would be activities to strengthen the preparation for the final project in future.